2017
DOI: 10.1080/09205063.2017.1296347
|View full text |Cite
|
Sign up to set email alerts
|

Folate-modified, indocyanine green-loaded lipid-polymer hybrid nanoparticles for targeted delivery of cisplatin

Abstract: Cisplatin is a potent antitumor drug, which is widely applied in clinical cancer treatment. However, cisplatin can hardly distinguish between healthy tissue and tumor tissue, resulting in serious toxic side effects. Indocyanine green (ICG) is a FDA-approved near-infrared (NIR) fluorescence dye which has been used in photothermal therapy and optically mediated diagnostic, but the application of ICG is limited by its concentration-dependent aggregation, poor aqueous stability in vitro, lack of target specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Moreover, the polymeric carriers offer prolonged and controlled drug release from the system and excellent stability profiles. Despite all of these properties, both liposomes and polymeric carrier systems have limitations in terms of drug stability, drug leakage, low loading capacity, and compatibility 8…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the polymeric carriers offer prolonged and controlled drug release from the system and excellent stability profiles. Despite all of these properties, both liposomes and polymeric carrier systems have limitations in terms of drug stability, drug leakage, low loading capacity, and compatibility 8…”
Section: Introductionmentioning
confidence: 99%
“…The amine SLN was prepared using a water-in-oil microemulsion according to a previousreport 30. In brief, the water-in-oil microemulsion was firstly prepared and stirred properly to obtain transparent solution.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, treatment of targeted NPs with 808 nm near infra-red laser irradiation induced substantial cell death by apoptosis and necrosis of MCF-7 cells compared with standard care therapy. 76 Using an ESE technique, a DOX-encapsulated LPHNP was constructed with PLGA-lecithin-DSPE-PEG and further decorated with DSPE-PEG-folate. It had been shown that folate-targeted NPs confer higher uptake and cytotoxicity in MCF-7 cells compared with nontargeted NPs.…”
Section: Folate-mediated Deliverymentioning
confidence: 99%